Challenges and opportunities of evaluating work based interprofessional learning: insights from a pediatric interprofessional training ward - Straub, Christine; Bode, Sebastian F. N.; Willems, Jana; Farin-Glattacker, Erik; Friedrich, Sebastian (Frontiers in Medicine, 2023)
Introduction Interprofessional collaboration among healthcare professionals is fostered through interprofessional education (IPE). Work-based IPE has demonstrated effectiveness within interprofessional training wards. We developed the Interprofessional Training Ward in Pediatrics (IPAPED) and employ a combination of established assessment tools and a newly created IPAPED questionnaire, directed at to assess both students’ learning experiences and program structure. This paper presents the development and analysis of the psychometric properties of the IPAPED questionnaire. Methods Nursing trainees and medical students participated in IPAPED. The IPAPED questionnaire was developed to complement established instruments, based on IPE frameworks. Interprofessional collaboration and communication were represented in subscales in part 1 of the questionnaire. Part 2 focused on the IPAPED program itself. Statistical analyses included calculation of internal consistency for part 1 and exploratory factor analyses for part 2. Results All IPAPED participants between November 2017 and November 2022 completed the questionnaire (n = 105). 94 of 105 questionnaires were analyzed. Internal consistency for part 1 was low (Cronbach’s α <0.58). Exploratory factor analyses revealed three distinct factors: teaching and learning material, interprofessional learning facilitation and professional guidance by nurses on the ward. Discussion Our results illustrate the challenge of performing high quality, theory based evaluation in a work-based setting. However, exploratory factor analyses highlighted the opportunity of focusing on both learning facilitators and staff on the wards to ensure a maximum learning output for participants. Developing program-specific questionnaires to gain insight into local structures has the potential to improve work-based IPE formats.